Women and water in global fiction - Staniland, Emma (New York, NY Routledge, 2023)
"Symbols and tropes of liquidity have long been connected to notions of the feminine, and therefore with orthodox constructions of femininity and womanhood. Underpinning these ideas is the vital importance of water as life force, which has given it a central place in cultural vocabularies worldwide. These symbolic economies, in turn, inform the discourses through which positive or negative associations of women with water come to bear impact on the social positioning of female gendered identities. Women and Water in Global Fiction brings together an array of studies of this phenomenon as seen in writing by and about women from around the world. The literature explored in this volume works to make visible, decodify, celebrate, and challenge the cultural associations made between female gendered identities and all kinds of watery tropes, as well as their consequences for key issues connected to women, society, and the environment. The collection investigates the roots of such symbolisms, examines how they inform women's place in the socio-cultural orders of diverse global cultures, and shows how the female authors in question use these tropes in their work as ways of (re)articulating female identities and their correlative roles"--
Introduction. Women and water: mapping a fluid terrain / Emma Staniland -- Mythologies and spiritualities of water. The Atlantis effect: the (re)claiming of women's space in the works and archives of Gloria Anzaldúa, tatiana de la tierra, and Lydia Cabrera / Sarah E. Piña -- Connecting women through water: Nalo Hopkinson's The salt roads (2003) as matrifocal speculative fiction / Leighan Renaud -- Grottoes and mermaids: fairy tales and transformations in Marie Nimier's Sirène (1985) and La plage (2016) / Rebecca Rosenberg -- "Water, water, everywhere, and not a drop to drink": spiritual renewal through destruction in Jewell Parker Rhodes's Hurricane (2011) / Angela Watkins -- Rivers, lakes and oceans. Of deserts and oceans: spaces of womanhood in the work of Malika Mokkedem / Elizabeth H. Jones -- Re-writing the colonial river: Fabienne Bayet-Charlton's Watershed (2005) and Murray River narratives / Brigid Magner and Emily Potter -- Ko wai koe?: identity and water in contemporary women's writing from Aotearoa New Zealand / Paula Morris -- Time and tide: topographies of trauma in Jhumpa Lahiri's The lowland (2013) / Kamil Naicker -- Watery subjectivities: exploring female Somali diasporic experiences of the sea in Cristina Ali Farah's Little mother (2011) and A dhow is crossing the sea (2011) / Ayan Salaad -- Metaphors of liquidity. Flowing along endlessly: Banana Yoshimoto's female protagonists and water as guiding force / Carrie Giunta -- Women, water and the house built on sand: tropes of liquidity in the feminist Latin American dictatorship novel: Cristina Peri Rossi's The ship of fools (1984) and Diamela Eltit's The fourth world (1988).
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Femininity in literature; Water in literature; Women in literature; Fiction -- 20th century -- History and criticism; Fiction -- 21st century -- History and criticism; Essays; Literary criticism